2016
DOI: 10.1007/s00277-016-2818-4
|View full text |Cite
|
Sign up to set email alerts
|

Expression of programmed cell death 1 and programmed cell death ligand 1 in extranodal NK/T-cell lymphoma, nasal type

Abstract: Programmed cell death-1 (PD-1) and programmed cell death-ligand 1 (PD-L1) are new therapeutic targets in cancer immunotherapy. The aim of this study was to investigate the clinicopathological characteristics of PD-1 and PD-L1 expression in extranodal natural killer/T‑cell lymphoma, nasal type (ENKTL). We performed PD-1 and PD-L1 immunostaining in 79 ENKTL biopsy samples and retrospectively analyzed medical records of all 79 patients from four tertiary referral hospitals. The expression of PD-1 and PD-L1 by tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
70
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(80 citation statements)
references
References 22 publications
6
70
0
4
Order By: Relevance
“…18 Another recent study also found that ENKTL patients with PD-L1 positivity in tumor cells had a trend toward improved OS compared with the negative control. 21 Contrary to these results, Bi et al and Muhamad et al found that PD-L1 expression in lymphoma cell tissue exhibited remarkably worse OS in ENKTL patients, 19 which was similar to the results of our study. Therefore, a single biomarker of PD-L1 for predicting the prognosis of ENKTL patients might have some limitations.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…18 Another recent study also found that ENKTL patients with PD-L1 positivity in tumor cells had a trend toward improved OS compared with the negative control. 21 Contrary to these results, Bi et al and Muhamad et al found that PD-L1 expression in lymphoma cell tissue exhibited remarkably worse OS in ENKTL patients, 19 which was similar to the results of our study. Therefore, a single biomarker of PD-L1 for predicting the prognosis of ENKTL patients might have some limitations.…”
Section: Discussionsupporting
confidence: 88%
“…[12][13][14][15][16][17] However, the results regarding the prognostic significance of PD-L1 in ENKTL are conflicting. [18][19][20][21][22] Based on these observations, the role of predicting the prognosis of PD-L1 has not been fully elucidated, and its use in combination with other biomarkers might enhance its predictive power.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the relationship between the expression of PD-L1 and the prognosis of patients with NHL remains controversial. Some studies have proposed that positive PD-L1 expression correlates with a poor prognosis 15-19 , while other studies have shown that positive PD-L1 expression does not correlate with prognosis or correlates with a good prognosis 20-23 . …”
Section: Discussionmentioning
confidence: 99%
“…NK/T-cell lymphoma cells express programmed death protein ligand 1 (PDL1), ligand of the inhibitory receptor PD1 on effector T-cells [82, 83]. PDL1 expression has been shown to be associated with EBV infection in lymphoma cells.…”
Section: Introductionmentioning
confidence: 99%